KEEFEKTIFAN MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KEMAMPUAN MEMAHAMI NOVEL - Sitti Harisah (Universitas Negeri Makassar, 2020)
The Effectiveness of Project-Based Learning Model on the Ability to Understand Novel. This study aims to identify significant differences between the application of the project-based learning model and those that do not apply the project-based learning model to the ability to understand the novels of Grade VIII students of SMP Negeri 19 Palu. This study uses a quantitative approach, the type of research used in this study is an experimental method with true experimental design research design in the form of pretest-posttest control group design. The results of the study note that the learning outcomes of the ability to understand the novel by using a project-based learning model before being given treatment, the average score of 67.24 pretest students after being given treatment, the average score of 74.84 posttest students. The results of learning the ability to understand the novel without using a project-based learning model, the average score of students pretest 63,80 after given direct learning, the average score of students posttest 69,32 and there is a significant difference in learning the ability to understand novels between learning the ability to understand novels using project-based learning models and those not using project-based learning models.